Decoherence and loss of entanglement in acoustic black holes - Lombardo, Fernando Cesar (2012)
We study the process of decoherence in acoustic black holes. We focus on the ion trap model proposed by Horstmann et al., but the formalism is general to any experimental implementation. For that particular setup, we compute the decoherence time for the experimental parameters that they proposed. We find that a quantum to classical transition occurs during the measurement, and we propose improved parameters to avoid such a feature. We also study the entanglement between the Hawking-pair phonons for an acoustic black hole while in contact with a reservoir, through the quantum correlations, showing that they remain strongly correlated for small enough times and temperatures. © 2012 American Physical Society.